Kinematics of ski alpin worldcup slalom racers by using AI-technologies and recalibrated cameras - Huber, A.; Hummel, C.; Spitzenpfeil, P.; Waibel, K.; Hock, T. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Knowledge of the kinematics of alpine ski racers is of great interest. Even at the elite level, the work of Reid (2009, 2010) in slalom and Spörri (2012) in giant slalom showed differences. But in their experimental design with several rotatable and tiltable cameras, only two complete turns could be analyzed. The aim of the method presented is to analyze the entire race course and all competitors.